The Influence of Profitability, Earnings Management, and Audit Opinion on the Timeliness of Financial Statement Submission - Sholikhah, Amaliatun; Sofwan, Ali (Jurnal Rekognisi Akuntansi, 2024)
This study aims to evaluate the effect of profitability, earnings management, and audit opinions on the timeliness of financial report submissions. The research focuses on non-primary consumer goods companies listed on the Indonesia Stock Exchange (IDX) between 2020 and 2022. A sample of 78 companies was selected using purposive sampling. Secondary data was utilized as the basis of the study. The analysis employed logistic regression, which included assessments such as model fit testing, overall model analysis, R² determination, regression coefficient evaluation, classification table accuracy, and hypothesis testing using the variables in the equation approach. The results indicate that profitability (X1) positively influences timely financial reporting, while earnings management (X2) and audit opinions (X3) do not show a significant effect. However, when analyzed together, profitability (X1), earnings management (X2), and audit opinions (X3) collectively affect the timeliness of financial report submissions. Companies are encouraged to prioritize punctual financial reporting, while future studies are recommended to incorporate variables like public ownership, auditor quality, and accountant opinion to enhance research precision